Pengaruh Produk, Harga, Lokasi, Dan Pelayanan Terhadap Keputusan Pembelian Konsumen Di Angkringan “37” - Kurniawan Wicaksana, Joan; Ajun Subarkah, Muhammad; Menno Subandy, Fatsha; Mundzier, Abdullah; Nova Dwi Putranto, Akmal (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to explain the effect of the product, price, location, and service of Angkringan 37 on the buying interest of STIE Widya Wiwaha students. The method used in this research is descriptive quantitative method. The sample in this study was taken as much as 15% of the 200 new students of STIE Widya Wiwaha in 2021/2022 and a sample of 32 students was obtained. The data collection technique used is a questionnaire. The results of the analysis of research data processing show that there is a positive and significant influence between the product, price, location, and service of Angkringan 37 on consumer behavior of STIE Widya Wiwaha students, the higher the quality of Angkringan 37 products, the higher the consumer behavior of students who are interested in buying. for example, the food and beverage products offered have quality and guaranteed cleanliness, and the location of the place provided is a strategic place which is near campus. Not only that, Angkringan 37 has a spacious and comfortable place so that students often do assignments or As well as there is a positive and significant influence between service attitudes on students purchasing power, the higher the influence of Angkringan 37 service attitudes, the higher the purchasing power of students, for example, Angkringan 37 services that prioritize customer satisfaction are able to increase customer satisfaction. inat students to be interested in buying food and beverages that are traded.